Rekonstruksi Paradigma Administrasi Negara Dan Aplikasinya: Orientasi Pemberdayaan Pemerintahan Daerah - Riyadi, Riyadi (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2010)
New paradigm that is currently used by the government seems to have led to the modern management approach. The direction and orientation of the State administration system which prioritizes the changes in public services is an emerging paradigm in the 21st century. The role of government in the context of classical administration (Old Public Administration) which is more to manage, control is directly centered on the government monopoly (Rowing), then shifted into the role of nature in the context of controlling the direction (steering) where the public role began to be actively involved. Shift in orientation was constructed in the context of a growing state administration towards the perspective of New Public Management (NPM). Then, development was shifted back to the government's role is to serve the public more, so the paradigm to be serving oriented. This paradigm is formulated as a perspective of the New Public Services (NPS) that are contextually much emphasized the importance of the role of government to direct all forms of execution of state administration tasks in order to realize a public service